The antidiabetic and antilipidemic effects of Hibiscus sabdariffa: A systematic review and meta-analysis of randomized clinical trials. (April 2020) - Bule, Mohammed; Albelbeisi, Ahmed Hassan; Nikfar, Shekoufeh; Amini, Mohsen; Abdollahi, Mohammad
Graphical abstract: Highlights: Data obtained from 8 articles (35 studies and/or data reports) were meta-analysed. Results of meta-analysis revealed that Hibiscus sabdariffa (HS) lowers FPG and LDL. The results of the study showed that HS does not affect blood TC, HDL, and TG. HS has antidiabetic activity while its lipid-lowering effect needs further study. Abstract: Hibiscus sabdariffa (HS) is a woody-based subshrub of the Malvaceae family which has various uses in traditional medicine. This review systematically evaluates the evidence from clinical trials on the antidiabetic activity of HS. A random-effects model was used to obtain summary estimates. Five outcome measure, including fasting plasma glucose (FPG), total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoproteins (LDL), and triglyceride (TG) were assessed in the study. The results of the overall pooled statics for the FPG level showed that there was a significant reduction in FPG (WMD = −3.964 mg/dL; 95% CI: −6.227 to −1.702 and P-value was 0.001) and in the level of LDL (WMD = −7.843 mg/dL; 95% CI: −14.337 to −1.350 and P-value was 0.018). However, the pooled estimate showed that there was no statistically significant change on the TC (WMD = −30.382 mg/dL; 95% CI: −66.752 to 5.989 and P value was 0.102), the HDL (WMD = 0.074 mg/dL; 95% CI: −1.986 to 2.135 and P value was 0.944) and the TG (WMD = −9.050 mg/dL; 95% CI, −30.819 to 12.719 and P value was 0.102) compared to the placebo. Egger's weighted regression P values suggested that there was no potential publication bias in the FPG ( P = 0.664), HDL (P = 0.065), LDL ( P = 0.677) and TG ( P = 0.232) but there was a publication bias in the TC (0.056). Therefore, the result of this meta-analysis clearly shows that HS has antidiabetic activity, whereas its lipid-lowering effect needs further study.